Differential Dimerization of Variants Linked to Enhanced S‐Cone Sensitivity Syndrome (ESCS) Located in the NR2E3 Ligand‐Binding Domain. Issue 6 (27th April 2015) - von Alpen, Désirée; Tran, Hoai Viet; Guex, Nicolas; Venturini, Giulia; Munier, Francis L.; Schorderet, Daniel F.; Haider, Neena B.; Escher, Pascal
<x xml:space="preserve">Abstract</x> The photoreceptor‐specific nuclear receptor NR2E3 represses cone‐specific gene expression in rod photoreceptor precursor cells. In ESCS (enhanced S‐cone sensitivity) patients, recessive mutations located in the ligand‐binding domain of NR2E3 impair homodimerization and interaction with retinal transcription factors, causing the generation of an increased number of 'blue' S‐cones and of defective hybrid rod photoreceptors ('cods'). NR2E3 efficiently dimerizes in patients affected by a 'forme fruste' of ESCS.